COLOUR TERMS: A PROBLEM FOR TRANSLATORS - Stanley-Thorne, Carol (Linguistica Atlantica, 2003)
Colour terms are universal in the sense that every language has a certain number of lexemes that are used to refer to colours in that culture. However, as Berlin and Kay (1969) discovered, languages vary in the number of basic colour terms they have, with that number ranging from as many as eleven to as few as two. The symbolic association of certain colours also varies from one language or culture to another. Therefore, translating material from one language to another poses a potential problem if the translator fails to take into account these differences.